2013
DOI: 10.1007/s13762-013-0251-y
|View full text |Cite
|
Sign up to set email alerts
|

High lipid content and productivity of microalgae cultivating under elevated carbon dioxide

Abstract: This study examined the cell growth rate, lipid contents, lipid productivity, chlorophyll a concentration, and carbon dioxide tolerance of Chlorella vulgaris under various cultivation conditions. The pH, concentration of carbon dioxide in media, and light intensity variables were manipulated to obtain high lipid productivity. The optimum conditions were at pH 7.0, 2,930 lux, and 30 % carbon dioxide. Biomass concentration reached 1,288, 1,130, and 1,083 mg L -1 at 15, 30, and 50 % CO 2 after 6 days, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 32 publications
(41 reference statements)
0
16
0
2
Order By: Relevance
“…grown in wastewaters (Komolafe et al, 2014), the green algae Botryococcus sp. and Chlorella vulgaris (Huang et al, 2013(Huang et al, , 2014 and the eustigmatophycean Nannochloropsis oculata (Sukenik et al, 1989). The effect of various environmental factors, such as pH, concentration of carbon dioxide in the medium, and irradiance were shown to impact on lipid production of microalgae (Huang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…grown in wastewaters (Komolafe et al, 2014), the green algae Botryococcus sp. and Chlorella vulgaris (Huang et al, 2013(Huang et al, , 2014 and the eustigmatophycean Nannochloropsis oculata (Sukenik et al, 1989). The effect of various environmental factors, such as pH, concentration of carbon dioxide in the medium, and irradiance were shown to impact on lipid production of microalgae (Huang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…and Chlorella vulgaris (Huang et al, 2013(Huang et al, , 2014 and the eustigmatophycean Nannochloropsis oculata (Sukenik et al, 1989). The effect of various environmental factors, such as pH, concentration of carbon dioxide in the medium, and irradiance were shown to impact on lipid production of microalgae (Huang et al, 2014). Beyond these environmental parameters, the application of nanomaterials (such as CaO and MgO nanoparticles) has been found to be effective catalysts of lipid synthesis and lipid extraction procedures (Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been reported that the nutritional content of bacteria and microalgae can be significantly modified by applying specific culture media and growth conditions (Loo et al . ; Huang & Su ).The cell walls of yeast comprise from 25 to 32% of the cell weight (Ferreira et al . ).…”
Section: Nutritional Value Of Microorganisms and Their Cellular Compomentioning
confidence: 99%
“…A clear solution was obtained after stirring for another 30 min. [17] After centrifugation and washing with deionized water three times, we added various amounts of deionized water to the microalgae to prepare an algae/water mixture (i.e., algae concentrate). Finally, Fe 3 O 4 nanoparticles were collected using a magnetic stone, washed with water and methanol repeatedly to remove excess ammonia, and stored in absolute ethanol to prevent oxidation of samples.…”
Section: Synthesis Of Tbd-functionalized Fe 3 O 4 @Silica Nanoparticlesmentioning
confidence: 99%